Kualitas Produk, Kualitas Pelayanan, Dan Live Musik Berpengaruh Terhadap Pengunjung Pada Kafe Bento Kopi UNS - Yuand Nova Erlangga; Indra Hastuti; Agus Suyatno (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The purpose of this study was to determine and analyze the effect of product quality, service quality and live on purchasing decisions at Bento Kopi UNS cafes. The approach used in this study is a quantitative and associative approach. The data analysis technique in this study used the Multiple Linear Regression analysis technique with a population of all visitors or consumers of UNS Coffee Bento Cafe and a sample of 100 respondents who had visited UNS Coffee Bento Cafe. The data collection technique in this study used a questionnaire and was processed using IBM SPSS Statistics 25. Conclusion The results of this study are the influence of the three independent variables on the dependent variable examined in this study. Product Quality, Service Quality, and Live Music have a positive and significant effect on Purchase Decisions at the Bento Kopi UNS Cafe